ANALYSIS OF THE RELATIONSHIP BETWEEN CREATIVITY AND SELF-EFFICACY IN SHAPING ENTREPRENEURIAL READINESS AMONG GENERATION Z IN MEDAN CITY - Asrika Winana Farida Ayu; Atika; Muhammad Ikhsan Harahap (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study seeks to determine the relationship of creativity and self-efficacy with entrepreneurial readiness among Generation Z in Medan City. Research Methodology: An associative design within a quantitative approach was applied. The sample comprised 100 Generation Z respondents residing in Medan City who were interested in entrepreneurship. Respondents were chosen through purposive sampling, and information was gathered by administering a Likert-scale questionnaire. SPSS version 29 was used to process the data through validity and reliability testing, classical assumption testing, Pearson correlation, multiple linear regression, t-tests, F-tests, and the coefficient of determination. Results: Partial testing showed a positive and significant relationship between creativity and entrepreneurial readiness (t = 4.594; p < 0.001). Self-efficacy likewise had a positive and significant relationship with entrepreneurial readiness (t = 3.136; p = 0.002). Joint testing also indicated a significant relationship of creativity and self-efficacy with entrepreneurial readiness (F = 4.125; p = 0.019). Together, the variables accounted for 7.8% of the variation in entrepreneurial readiness, leaving 92.2% associated with factors beyond the study. Conclusions: Generation Z respondents who demonstrate greater capacity to produce and develop ideas and stronger confidence in their business capabilities generally show greater entrepreneurial readiness. Nevertheless, the model's small contribution suggests that creativity and self-efficacy alone do not provide a comprehensive explanation of entrepreneurial readiness. Limitations: The study covers only 100 Generation Z respondents in Medan City selected through purposive sampling. A cross-sectional design and self-reported questionnaires further restrict the generalizability of its findings and prevent causal conclusions from being drawn. Contributions: By emphasizing entrepreneurial readiness instead of focusing solely on entrepreneurial intention, this study broadens research on entrepreneurship among Generation Z. Its findings support incorporating idea-development activities and business simulations into entrepreneurship programs to reinforce participants' self-efficacy.